Parental environments and interactions with conspecifics alter salinity tolerance of offspring in the annual Medicago truncatula. (30th July 2013) - Castro, Brenna M.; Moriuchi, Ken S.; Friesen, Maren L.; Badri, Mounawer; Nuzhdin, Sergey V.; Strauss, Sharon Y.; Cook, Douglas R.; von, Eric; Klinkhamer, Peter
Summary Based on expectations of the stress‐gradient hypothesis for conspecific interactions, stress‐sensitive genotypes may be able to persist in stressful environments when positive interactions between individuals occur under stressful environments. Additionally, we test how parental environmental effects alter responses to stress and outcomes of conspecific interactions in stress. While the stress‐gradient hypothesis focuses on plant growth, earlier flowering may provide stress avoidance in short‐lived organisms. We studied responses to soil salinity and conspecific neighbour using genotypes of Medicago truncatula (Fabaceae) originating from saline or non‐saline environments, utilizing seeds from parental plants grown in saline or non‐saline environments. During the early stages of reproduction, we quantified leaf number, as a measure of vegetative growth, and number of flowers, as a measure of early reproduction potential. Based on leaf counts, non‐saline genotypes were better competitors than saline‐origin genotypes and benefited from neighbouring plants in saline environments. This positive interaction was detected only when seeds were matured on parental plants grown in non‐saline environments. Saline‐origin genotypes displayed greater salinity tolerance in early flowering than non‐saline genotypes. Plants with neighbours had greater early flowering, regardless of origin, consistent with facilitative interactions in stressful environments. Transgenerational plastic responses influenced neighbouring plant interactions on plant growth, and results suggest that facilitative interactions may be transient only persisting for one generation. However, earlier flowering of non‐saline genotypes when grown with a neighbouring plant is consistent with facilitative interactions resulting in reproductive benefits in saline environments, if earlier flowering is favoured in saline environments. Synthesis. Adaptation to stressful environments allows tolerant genotypes to persist in these environments. Less appreciated is that stress‐sensitive genotypes lacking such adaptations may persist in stressful environments via positive interactions with other individuals. Thus, positive interactions between individuals may explain the persistence of stress‐sensitive genotypes within a population adapted to stressful environments.